The use of silica-immobilized brown alga (Pilayella littoralis) for metal preconcentration and determination by inductively coupled plasma optical emission spectrometry - Carrilho, ENVM; Nobrega, J. A.; Gilbert, T. R. (Elsevier B.V., 2003)
The brown alga Pilayella littoralis was used as a new biosorbent in an on-line metal preconcentration procedure in a flow-injection system. Al, Co, Cu and Fe were determined in lake water samples by inductively coupled plasma optical emission spectrometry (ICP-OES) after preconcentration in a silica-immobilized alga column. Like other algae, P. littoralis exhibited strong affinity for these metals proving to be an effective accumulation medium. Metals were bound at pH 5.5 and were displaced at pH < 2 with diluted HCl. The enrichment factors for Cu-II, Fe-III, Al-III and Co-II were 13, 7, 16 and 11, respectively. Metal sorption efficiency ranged from 86 to 90%. The method accuracy was assessed by using drinking water certified reference material and graphite furnace atomic absorption spectrometry (GFAAS) as a comparison technique. The column procedure allowed a less time consuming, easy regeneration of the biomaterial and rigidity of the alga provided by its immobilization on silica gel. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Pilayella littoralis; biosorbent; metal preconcentration; flow injection; ICP-OES; GFAAS